Metaphorical understanding of Jesus’ resurrection - Jones, Christopher D. (Verbum et ecclesia, 2025)
In addition to being a central tenet of Christianity, Jesus Christ’s resurrection is a powerful metaphor that relates to the human experience of change, hope and renewal. Although this event is frequently regarded literally, it can also be understood metaphorically to explore themes such as personal and collective transformation. This article seeks to explore some of these multifaceted meanings by considering historical contexts of relevant biblical texts (mainly the four gospels and Paul) and literary, artistic and cultural expressions, culminating in the ongoing relevance of the resurrection narrative. Intradisciplinary and/or interdisciplinary implications: The article illustrates the need for interpreting the ancient references to the resurrection of Jesus metaphorically. Interpreting these mythological descriptions in a realistic, historical and literal sense renders them anachronistic in our time. Resurrection, viewed metaphorically, can, however, still convey rich and meaningful perspectives. It can still be a core element of one’s existential belief.